SIRT1 regulates hypoxia-induced oxidative stress in cardiomyocytes via PI3K/MTOR signaling: SIRT1 regulates hypoxia-induced oxidative stress - Ma, Bocong; Guo, Bingyan; Chen, Zhiyan; Li, Yongjun (Cellular and Molecular Biology, 2022)
This work was developed to investigate the activation of silent information regulator 1 (SIRT1) to regulate hypoxia-induced oxidative stress in cardiomyocytes through the PI3K/MTOR signaling pathway. For this purpose, 30 SD healthy rats were selected, and 10 of them were randomly selected as the control group. The remaining 20 rats were established as acute myocardial infarction model rats, and randomly divided into model group and activated SIRT1 group. Interventions were performed on rats in each of the 3 groups. ROS staining, inflammatory factors [IL-6, IL-1β levels], H9c2 cell viability, Caspase3 and Caspase8 activity, antioxidant enzyme indexes [SOD, CAT, MDA levels], SIRT1, PI3K, MTOR, HIF-1α, HO-1, GLUT1 mRNA expression were compared between groups. Results showed that IL-6 and IL-1β levels were abnormally elevated in the model group compared with the control group (P<0.05). IL-6 and IL-1β levels decreased in the activated SIRT1 group compared with the model group (P<0. 05). H9c2 cell viability decreased and Caspase3 and Caspase8 activities increased in the model group compared with the control group(P <0.05). H9c2 cell viability increased and Caspase3 and Caspase8 activities decreased in the activated SIRT1 group compared with the model group (P<0.05). SOD and CAT levels were abnormally decreased and MDA levels were abnormally increased in the model group compared with the control group (P<0.05). SOD and CAT levels were abnormally increased and MDA levels were decreased in the activated SIRT1 group compared with the model group (P<0.05). PI3K and SIRT1 expression decreased and MTOR expression increased in the model group compared with the control group (P < 0. 05). PI3K and SIRT1 expression increased and MTOR expression decreased in the activated SIRT1 group compared with the model group(P<0.05). The expression of HIF-1α, HO-1 and GLUT1 mRNA increased in the model group compared with the control group, and the difference was statistically significant (P <0.05). The expression of HIF-1α, HO-1, and GLUT1 mRNA decreased in the activated SIRT1 group compared with the model group, and the difference was statistically significant (P<0.05). It was concluded that the activation of SIRT1 can regulate PI3K/MTOR signaling pathway, thus reducing hypoxia-induced oxidative stress in cardiomyocytes, inflammatory conditions and enhancing cardiomyocyte viability, with better intervention effects.